PENGARUH SIKAP BELAJAR DAN MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR PADA PELAJARAN PPKN KELAS X - Siska Rahayu; Okianna Okianna; Thomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to determine the Effect of Learning Attitudes and Motivation of Class X MAS Darul Ulum Students on Learning Outcomes in Civics Education Lessons. This study used a descriptive research method with a quantitative approach. The data were collected with indirect communication and documentary study techniques by using questionnaires and documentation tools. From the results of the analysis, each indicator of attitude and learning motivation of students of Class X MAS Darul Ulum showed variation in percentage. The effect of attitudes is significant on student learning outcomes by 1.14%, as well as the effect of motivation is significant by 1.29%. Based on the R square, the significance of the attitudes and motivation on the students learning outcomes is 0.29% with tcount of 8.370 and the significance value (Sig.) of 0,000. Since tcount (8.370) > ttable (1.701), therefore, the null hypothesis is declined, and the alternative hypothesis is accepted. Keyword : Learning Attitudes, Learning Motivation, Learning Outcomes